2021
DOI: 10.1002/ppul.25357
|View full text |Cite
|
Sign up to set email alerts
|

Meconium stained amniotic fluid exposure and long‐term respiratory morbidity in the offspring

Abstract: Objective Meconium stained amniotic fluid (MSAF) is a well‐established risk factor for neonatal short‐term respiratory complications. Little is known regarding the long‐term morbidity. We investigated the possible association between MSAF and offspring respiratory morbidity. Methods A population‐based, cohort study of singleton deliveries occurring between 1991 and 2014 at a sole regional tertiary medical center was performed. Incidence of offspring respiratory related hospitalizations up to the age of 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Two large studies reported that the incidence was approximately 14.7% (35,897/243,725; 35,609/242,342). 4 , 5 Before 37 weeks, MSAF was less common, occurring in approximately 4.3–6.9% of pregnancies, but with increasing gestation week, a higher incidence of MSAF was observed, in approximately 10.0–14.6% of pregnancies (listed in Table S1 ), 6 which was in accordance with previous studies showing that MSAF most commonly occurred from 38–41 weeks of gestation. 7 …”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Two large studies reported that the incidence was approximately 14.7% (35,897/243,725; 35,609/242,342). 4 , 5 Before 37 weeks, MSAF was less common, occurring in approximately 4.3–6.9% of pregnancies, but with increasing gestation week, a higher incidence of MSAF was observed, in approximately 10.0–14.6% of pregnancies (listed in Table S1 ), 6 which was in accordance with previous studies showing that MSAF most commonly occurred from 38–41 weeks of gestation. 7 …”
Section: Introductionsupporting
confidence: 90%
“…Two large studies reported that the incidence was approximately 14.7% (35,897/243,725; 35,609/242,342). 4,5 Before 37 weeks, MSAF was less common, occurring in approximately 4.3-6.9% of pregnancies, but with increasing gestation week, a higher incidence of MSAF was observed, in approximately 10.0-14.6% of pregnancies (listed in Table S1), 6 which was in accordance with previous studies showing that MSAF most commonly occurred from 38-41 weeks of gestation. 7 According to the standard grading system for meconium, MSAF can be classified into 3 grades: I (translucent, light green or yellow flesh), II (opalescent, deep green and light yellow, brown), and III (opaque and deep green), and it can also be classified as thin or thick based on the different solid contents.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation